Daya Terima dan Kandungan Gizi Mi Kremes Substitusi Mocaf (Modified Cassava Flour), Hati Ayam dan Biji Labu Kuning untuk Mencegah Anemia - Dinis Puspita Rakhman; Annis Catur Adi (Universitas Airlangga, 2023)
Background: Iron deficiency (Anemia) is a major health problem by Indonesian youth. Anemia needs to be treated appropriately because it can have a long term negative impact on the quality life of adolescents. Mocaf, chicken liver, and pumpkin seeds are food source of protein and iron that can be processed into mi kremes as a snack to prevent anemia. Objectives: The purpose of this study was to analyze acceptability, protein and iron content of mi kremes with substitued of mocaf, chicken liver, and pumpkin seeds. Methods: This research used pure experimental with completely randomized design (CRD). There are 5 formulas which are then selected for 3 selected formulas that will be further investigated. 3 formulas is control formula (F0) and 2 modified formulas (F3, F4). The total of substitutions F3 (mocaf 15 g, chicken liver flour 10 g, and pumpkin seeds flour 15 g) and F4 (mocaf 20 g, chicken liver flour 10 g, and pumpkin seeds flour 10 g). This research used 25 untrained panelists namely young women aged 10-18 Results: The results of acceptability test showed that the most preferred modified formula by untrained panelists is F3. The protein and iron content per 100 g mi kremes was 8,02 g and 3,11 mg. There was a significant difference between F0 and F4 in taste characteristics (p = 0,003). Conclusion: The formula with the highest acceptance is F3. One serving of F3 (70 g) can meet 10-15% of the protein and iron needs in young women aged 10-18.